2017
DOI: 10.1155/2017/4354826
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Multiple Sclerosis in Tunisia: A Retrospective Study over 11 Years

Abstract: Introduction Pediatric multiple sclerosis (pMS) is a rare demyelinating disorder with an onset before the age of 18 years. In this study, we aimed to investigate the characteristics of pMS in Tunisian children. Patients and Methods We conducted a retrospective study over 11 years (2005–2016) including all patients diagnosed with pMS according to the International Pediatric Multiple Sclerosis Study Group (IPMSSG) criteria of 2012 and followed up in a tertiary care research center. Epidemiological, clinical, neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…The first case of secondary progressive multiple sclerosis was a girl with disease onset at age 4 years who converted from relapsing-remitting to secondary progressive multiple sclerosis during the pediatric period (age of conversion to secondary progressive multiple sclerosis not reported). 25 This individual had an Expanded Disability Status Scale score 4.5 at disease onset and an Expanded Disability Status Scale score of 3.5 at last follow-up. The second case of secondary progressive multiple sclerosis was a girl aged 17 years 11 months who had been followed for 38 months, age and Expanded Disability Status Scale score at disease onset not reported, age of conversion to secondary progressive multiple sclerosis not reported, and Expanded Disability Status Scale score 2.5 at last follow-up.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The first case of secondary progressive multiple sclerosis was a girl with disease onset at age 4 years who converted from relapsing-remitting to secondary progressive multiple sclerosis during the pediatric period (age of conversion to secondary progressive multiple sclerosis not reported). 25 This individual had an Expanded Disability Status Scale score 4.5 at disease onset and an Expanded Disability Status Scale score of 3.5 at last follow-up. The second case of secondary progressive multiple sclerosis was a girl aged 17 years 11 months who had been followed for 38 months, age and Expanded Disability Status Scale score at disease onset not reported, age of conversion to secondary progressive multiple sclerosis not reported, and Expanded Disability Status Scale score 2.5 at last follow-up.…”
Section: Resultsmentioning
confidence: 91%
“…Four studies provided Expanded Disability Status Scale scores for individual cases (n=168). 16,18,24,25 Of these cases, 5/168 (3.0%) children with pediatric-onset multiple sclerosis reached an Expanded Disability Status Scale score of 5.5 or higher during the various follow-up periods. Gudbjornsson et al 34 reported a median Expanded Disability Status Scale score of 0.0 (range 0.0-4.0) for 8 cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(21) çalışmasında olguların %65'inde ilk yıl içinde relaps görülmüş, yeterli süre izlenebilen olgulardan hesaplanan ilk 3 yılda her hasta için yıllık relaps oranı 0,95 olarak saptanmıştır. Önceki çalışmalarda pediatrik MS olgularında erişkin MS olgularına göre yıllık relaps oranı anlamlı olarak daha yüksek saptanmıştır (1,1'e karşı 0,4), bunda pediatrik popülasyonun santral sinir sisteminde immün hücrelerin daha fazla bulunması ve immün hücrelerinin daha yoğun immün cevaba sahip olması etken olabilir (23).…”
Section: Materyal Ve Metodunclassified